Conservative medical intervention as a complement to CDT for BCRL therapy: a systematic review and meta-analysis of randomized controlled trials - Deng, Chuyu; Wu, Zhiguo; Cai, Zijie; Zheng, Xiaoyan; Tang, Chunzhi (Frontiers in Oncology, 2024)
The effect of the first-line complex decongestive therapy (CDT) for breast cancer-related lymphedema (BCRL) depending on various factors, forces patients to seek additional treatment. Therefore, this meta-analysis is to evaluate the effect of different conservative medical interventions as a complement to CDT. This is the first meta-analysis that includes various kinds of conservative treatments as adjunctive therapy to get broader knowledge and improve practical application value, which can provide recommendations to further improve BCRL patients' health status. METHODS: RCTs published before December 18, 2023, from Pubmed, EMBASE, Cochrane Library, and Web of Science databases were searched. RCTs that compared the effect of conservative medical intervention were included. A random effects or fixed effects model was used based on the heterogeneity findings. Study quality was evaluated using the Cochrane risk of bias tool. RESULTS: 16 RCTs with 690 participants were included, compared laser therapy, intermittent pneumatic compression (IPC), extracorporeal shock wave therapy(ESWT), electrotherapy, ultrasound, diet, or combined with the synbiotic supplement, traditional Chinese medicine(TCM), continuous passive motion (CPM), negative pressure massage treatment (NMPT). The results revealed that conservative medical intervention as complement to CDT had benefits in improving lymphedema in volume/circumference of the upper extremity [SMD = -0.30, 95% CI = (-0.45, -0.15), P < 0.05, I 2 =51%], visual analog score (VAS) for pain[SMD= -3.35; 95% CI(-5.37, -1.33), P <0.05, I 2 =96%], quality of life[SMD= 0.44; 95% CI (0.19, 0.69); P <0.05, I 2 =0], DASH/Quick DASH [SMD= -0.42; 95% CI (-0.70, -0.14); P <0.05, I 2 =10%] compared with the control group. Subgroup analysis revealed that laser